2022
DOI: 10.1021/acsmacrolett.2c00713
|View full text |Cite
|
Sign up to set email alerts
|

Self-Initiated Photopolymerization of Anti-Inflammatory Zwitterionic Hydrogels with Sustained Release

Abstract: Hydrogels are three-dimensional networks of hydrophilic polymers that have garnered significant attention as wound-healing materials. Many synthetic hydrogels are fabricated using a radical polymerization approach that requires an initiator molecule that is often photo-or thermosensitive. Initiator-free hydrogels are an emerging area of research that focuses on hydrogel fabrication that occurs in the absence of an initiator or cross-linker molecule, making these hydrogels highly relevant in tissue engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition to their sustained release behavior, the hydrogels also improve the rate of wound healing in an in vivo diabetic mouse model without the use of a therapeutic, indicating that the hydrogel itself interacts with cells to improve wound healing outcomes (Figure 3). 57,58 Although the gel + therapeutic condition increases the rate of healing significantly faster, the gel alone condition (40:60 SBMA:HEMA) also improved wound healing rate compared to the PBS control, indicating that material signaling can improve regenerative outcomes in vivo without a therapeutic (Figure 3A,B). This behavior can likely be attributed to the ability of zwitterionic polymers to resist nonspecific protein adsorption, which reduces the prolonged inflammatory response during chronic wound healing.…”
Section: Other Methodsmentioning
confidence: 99%
“…In addition to their sustained release behavior, the hydrogels also improve the rate of wound healing in an in vivo diabetic mouse model without the use of a therapeutic, indicating that the hydrogel itself interacts with cells to improve wound healing outcomes (Figure 3). 57,58 Although the gel + therapeutic condition increases the rate of healing significantly faster, the gel alone condition (40:60 SBMA:HEMA) also improved wound healing rate compared to the PBS control, indicating that material signaling can improve regenerative outcomes in vivo without a therapeutic (Figure 3A,B). This behavior can likely be attributed to the ability of zwitterionic polymers to resist nonspecific protein adsorption, which reduces the prolonged inflammatory response during chronic wound healing.…”
Section: Other Methodsmentioning
confidence: 99%
“…These results suggested that SBMA played an important role in the quick gelation process. It has been reported that SBMA could be self-initiated, 54 which may facilitate the free radical polymerization during the hydrogel preparation. As the hydrophobic methacrylate groups from SBMA could form hydrophobic domains, 55 the effective concentration of polymerizable groups there was relatively high, leading to an increased rate of the propagation reaction in polymerization.…”
Section: Preparation Of the Zwitterionic Hydrogelmentioning
confidence: 99%
“…Initiator-free systems have attracted great interest in the field of biomaterials due to their low cost, ease of upscaling production, high cytocompatibility, and low bioirritability, which has the potential to improve their ability to be translated into clinical or commercial applications. [58][59][60] However, the method of free radical photopolymerization of hydrogels is inhibited by oxygen, the control of cross-linkage mechanics is poor, and there are unreacted unsaturated bonds formed with biological materials and internal heterogeneity caused by irregular chain polymerization. [61,62] Another method, known as bio-orthogonal click reactions, produces structurally homogenous hydrogels with minor network flaws by a stepwise growth process involving orthogonal reactivity and polymerization reactions.…”
Section: Photo-crosslinked Hydrogelsmentioning
confidence: 99%